The use of banana trunks ash as cement replacement in mortar - Muhamad Lukman Hakim, Wahab (2015)
Nowadays, construction industry had growing up to become one of important industry in Malaysia. One of the important components in construction industry is mortar, which act as a binder to give strength to hold bricks with different size and also to patch hole in the wall of the building. As stated, this research is done to determine the best portion of banana trunks ash can be replace the cement in the making of mortar and also to determine the strength of mortar that can be achieve by using banana trunks ash. The banana trunks ash is an agriculture waste that has potential to replace one of construction material which is cement. Banana trunks ash contains a pozzolanic reaction that usually occurs in Portland cement. The banana trunks ash was produced from the process of burning the dried banana trunk into furnace at 500°C for 2 hours. In this research, compression test was conducted to determine the compressive strength of the mortars that replace the cement with 1%, 2% and 3% weight of banana trunks ash. A total of 27 specimens with size of 50mm x 50mm x 50mm were prepared by using timber mould. All the specimens were curing for 7 days, 14 days and 28 days by using water curing method. Based on the test and analysis that have be done, the normal mortar has highest compressive strength at 28 days with 15.484MPa, followed by 2% with 9.149MPa,1% with 8.349MPa and lastly,3% with 8.709MPa.